Pathogenicity, Development and Reproduction of The Entomopathogenic Nematode Steinernema sp., in Mealworm Tenebrio molitor - Baliadi, Yuliantoro; Sastrahidayat, Ika Rochdjatun; Djauhari, Syamsuddin; Rahardjo, Bambang Tri (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2011)
The pathogenicity, development and reproduction of Steinernema sp., isolate Skpr-20/Str, were studied using Tenebrio molitor. Results revealed that pathogenicity, development and reproduction were significantly influenced by nematode doses. Although the number of invading IJs increased with increasing dose, percentage penetration declined. The IJs reached adulthood within 3 days. Females laid eggs from day 4-7. All eggs remaining inside uterus develop inside the maternal body. The first female bearing endotokia matricida was observed on day 5. In a sand-based assay, nematode was more pathogenic at lower dose instead of higher ones, where optimum dose was 80 nematodes per larva and average number of progeny per female was 5438. Under crowded conditions, development proceeds to IJ stage instead of the J3. The average length and width decreased with increasing of nematode doses. The IJ produced in cadavers infested with 640 nematodes per larva was significantly smaller (492 Â± 6.4 Âµm) than offspring from other doses. The number of days which nematodes first emerged from the cadavers decreased with increasing dose. IJ first emerged at the average of 10-13 days at high IJ densities. It is concluded that the wide experimental characteristic of EPNs is also true for Steinernema sp., isolate Skpr-20/Str.Keywords: development, emergence period, endotokia matricida, entomopathogenic nematode, isolation, pathogennicity, Steinernema sp., isolate Skpr- 20/Str